Online or Offline? How Smog Pollution Affects Customer Channel Choice for Purchasing Fresh Food - Liang, Jing; Ma, Jiangshui; Zhu, Jing; Jin, Xu (Frontiers in Psychology, 2021)
Due to fresh foods’ unique characteristics, where quality, freshness, and perishability are the main concerns, consumers are more inclined to choose offline channels for purchasing foods. However, it is not well understood how these behaviors are affected by the adverse external environment, e.g., smog pollution. Fine particulate matters (PM2.5) on smog days would irritate the respiratory tract and pose health risks to people, triggering negative emotions such as sadness and depression. People tend to stay in a clean indoor environment on smog days. An adverse external environment is causing a gradual change in people’s habits and emotions. Still, its impact on shopping behaviors is a complex process in need of further study. The study fills this gap by examining the impact of smog pollution on consumers’ channel selection behaviors. Based on data from an e-commerce retailer that operates in both online and offline channels. We find that (1) the degree of smog pollution has a significant positive effect on online channel purchasing at aggregated store-, product- and individual- levels; (2) moreover, the retailer’s in-store interactive activities would restrain this positive relationship; (3) variation of product pricing and customers’ healthy eating tendency would pronounce the positive association between smog and online purchasing. These results can serve as a reference for retailers to adjust channel strategies in the face of harsh external conditions.